Health-Related Physical Fitness among Young Goalball Players with Visual Impairments. (July 2016) - da Cunha Furtado, Otávio Luis Piva; Morato, Márcio Pereira; Potenza, Michael; Gutierrez, Gustavo Luiz
Introduction: The purpose of our study was to determine the passing rates on health-related physical fitness tests of young goalball players. More specifically, we compared their passing rates according to gender and visual impairment classification. Methods: Participants included 40 Brazilian goalball players with visual impairments (20 female [B1 = 7, B2 = 8, B3 = 5]; 20 male [B1 = 6, B2 = 4, B3 = 10]), with a mean age 17.3 (SD = 1.6). The Brockport Physical Fitness Test, a health-related, criterion-referenced protocol, was employed to evaluate percentage of body fat, shoulder stretch, back-saver sit and reach, trunk lift, curl-ups, push-ups, and the one-mile run or walk. Results: A significant difference was found in passing rates between genders only in the one-mile run or walk. More than half the participants were able to pass in at least four out of the seven tests. No significant differences were found between groups regarding the proportion of athletes who reached the protocol standards. Discussion: Irrespective of gender or visual impairment classification, the participants of this study had high passing rates on most tests. Nonetheless, athletes had low passing rates on specific areas (cardiovascular and muscular strength), which need to be acknowledged. Future studies with a bigger sample could seek to determine the effects of specific training regimens not only on youths, but also on adult groups. Implications for practitioners: As a Paralympic sport likely to be of interest to visually impaired children and adolescents, goalball seems to be a feasible game to support the achievement of ideal physical activity levels in this population, leading to higher levels of health-related physical fitness.